2023
DOI: 10.3390/ijms241713561
|View full text |Cite
|
Sign up to set email alerts
|

Marine Bacterioplankton Community Dynamics and Potentially Pathogenic Bacteria in Seawater around Jeju Island, South Korea, via Metabarcoding

Hyun-Jung Kim,
Kang Eun Kim,
Yu Jin Kim
et al.

Abstract: Understanding marine bacterioplankton composition and distribution is necessary for improving predictions of ecosystem responses to environmental change. Here, we used 16S rRNA metabarcoding to investigate marine bacterioplankton diversity and identify potential pathogenic bacteria in seawater samples collected in March, May, September, and December 2013 from two sites near Jeju Island, South Korea. We identified 1343 operational taxonomic units (OTUs) and observed that community diversity varied between month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…3.5 Specificity of ICTS Kim et al (2023) showed that the abundance of Vibrio was higher in the samples from the marine bathing beach, and we selected V. parahemolyticus, V. vulnifcus, V. harveyi, V. anguillarum, and E. tarda to detect the specificity of the developed method for enterococci bacteria. After the specificity of ICTS was tested by enterococci and Vp, Vv, Vh, and Et, the ICTS prepared with artificial multi-epitope antibody showed that seven kinds of enterococci were positive.…”
Section: Determination Of the Labeling Conditions Of Colloidal Goldmentioning
confidence: 99%
“…3.5 Specificity of ICTS Kim et al (2023) showed that the abundance of Vibrio was higher in the samples from the marine bathing beach, and we selected V. parahemolyticus, V. vulnifcus, V. harveyi, V. anguillarum, and E. tarda to detect the specificity of the developed method for enterococci bacteria. After the specificity of ICTS was tested by enterococci and Vp, Vv, Vh, and Et, the ICTS prepared with artificial multi-epitope antibody showed that seven kinds of enterococci were positive.…”
Section: Determination Of the Labeling Conditions Of Colloidal Goldmentioning
confidence: 99%